Refeeding syndrome as a serious complication of a treatment of patients with anorexia nervosa - a literature review - Marko, Natalia; Niewiadomska, Jagoda; Furtak, Daria; Grela, Wiktor; Tulej, Dawid; Głogowska, Paulina; Dziedzic, Alicja; Górska, Aleksandra; Gniaź, Natalia; Marciniuk, Dominika (Journal of Education, Health and Sport, 2025)
Introduction and purpose of the work: Refeeding syndrome (RFS) is an acute, life-threatening hormonal and metabolic disorder that appears in the initial period of treatment in patients with anorexia nervosa with moderate or severe malnutrition as a result of inadequately managed nutritional therapy. The purpose of this article is to describe and draw special attention to this serious complication, as well as to summarize the latest research and guidelines on nutritional rehabilitation in these patients. Information was collected from the English-language databases Google Scholar and PubMed.<span data-ccp-props="{"201341983":0,"335559738":25,"335559739":25,"335559740":360,"335572071":0,"335572072":0,"335572073":0,"335572075":0,"335572076":0,"335572077":0,"335572079":0,"335572080":0,"335572081":0,"335572083":0,"335572084":0,"335572085":0,"335572087":0,"335572088":0,"335572089":0,"469789798":"nil","469789802":"nil","469789806":"nil","469789810":"nil","469789814":"nil"}"> <span data-ccp-props="{"201341983":0,"335559738":25,"335559739":25,"335559740":360,"335572071":0,"335572072":0,"335572073":0,"335572075":0,"335572076":0,"335572077":0,"335572079":0,"335572080":0,"335572081":0,"335572083":0,"335572084":0,"335572085":0,"335572087":0,"335572088":0,"335572089":0,"469789798":"nil","469789802":"nil","469789806":"nil","469789810":"nil","469789814":"nil"}"> State of knowledge: Due to the chronic state of malnutrition and significant electrolyte and vitamin deficiencies in patients with anorexia nervosa, the process of refeeding is associated with the risk of acute electrolyte disturbances such as hypophosphatemia, hypokalemia, and hypomagnesemia, which can lead to severe cardiac, respiratory, hematologic, and neurological complications. Symptoms usually appear within 2 to 5 days of initiating refeeding. Currently, the lack of a standardised definition and the non-specificity of the symptoms make it difficult to both estimate the incidence and diagnose refeeding syndrome. Summary: The latest research proves that, compared to previous protocols, a safe start to the nutritional process may be based on a moderately increased starting caloric intake, as this results in faster weight gain and shortens the treatment time. HCR has been proven to be safe and effective, without significantly increasing the risk of refeeding syndrome. Additionally, it is crucial to monitor the levels of phosphates, magnesium and potassium and early supplementation of these electrolytes to prevent and alleviate the symptoms of refeeding syndrome. Further research is still needed to optimize nutritional protocols that take into account individual patient needs and minimize the risk of refeeding syndrome.